Perencanaan Kapasitas Produksi Industri Pakan Ternak dengan Metode Theory of Constraints - Ikhwana, Andri; Taptajani, Dedi Sa’dudin; Nurul Hikmah, Ikmal Wahyudi (Jurnal Kalibrasi, 2024)
To convert production input into production output, the production system consists of a collection of interconnected subsystems. These production inputs include raw materials, machines, labor, capital, and information, while production outputs are products from by-products, such as waste, information, etc. The capacity to produce animal feed that does not meet consumer demand is the aim of this research. A quantitative approach is used in this research, which involves direct observation or observation. In addition, the problem identification method uses the Theory of Constraints to identify parts of the work station that experience obstacles or barriers. optimize production capacity to achieve production goals or meet customer demand. The research results show that the problem is caused by the milling machine which has a smaller capacity and there is only 1 milling machine, resulting in a bottleneck. Based on these problems, knowing the size of the market demand shortage is 51.53%, which means there is still 49.47% of market demand that cannot be met. Then, the weighing SK workload is 82.8%, the sorting SK workload is 85%, the drying SK workload is 89.4%, the milling machine SK workload is 117.9%, the packaging SK workload is 91.2%. Determination of the bottleneck can be seen from the highest percentage of workload, namely on the SK milling machine at 117.9%. So, to overcome this bottleneck, a routing sheet calculation is carried out to find out the number of machines that need to be added to the milling machine work station. So that consumer demand can be met by adding 2 additional milling machines, as well as the cost of adding machines to the milling machine work station of IDR 12,802,918.